Diseño de propuesta de mejoramiento de riesgos ocupacionales en la empresa de lácteos IBEL en el municipio de Belén (2023)
The main objective of this academic work is to design a proposal to prevent occupational risks in the production process of the company "DAIRY IBEL" of the municipality of Belén, developed with methodology in mixed type research, in descriptive approach, exploratory and applied, with which three phases were carried out: the initial diagnosis, with the collection of photographic evidence, checklist under standard NTC 4114 supported by direct observation carried out in the field work and interviews; Once the diagnosis was made, the current working conditions and the association between the elements of the productive process and the health and safety of workers were identified, and opportunities for improvement were also identified on which proposals were established at the end of the project.